Predictors of Developmental Patterns of Obesity in Young Children - O'Connor, Thomas G.; Williams, Jason; Blair, Clancy; Gatzke-Kopp, Lisa M.; Francis, Lori; Willoughby, Michael T. (Frontiers in Pediatrics, 2020)
Introduction: The current study characterizes longitudinal patterns in obesity and their prediction from developmental programming and social determinant hypotheses of childhood obesity. Materials and Methods: The data are based on the Family Life Project, a prospective longitudinal study of 1,292 families recruited from low-income, racially diverse, rural communities in Pennsylvania and North Carolina. Prenatal, perinatal, and postnatal risks for childhood obesity were collected from 2 months of age; in-person assessments of child growth were used to identity obesity on multiple occasions from 24 to 90 months of age. Results: Two major novel findings emerged. First, longitudinal analyses identified four distinct obesity development profiles: stable obesity, later-onset obesity, moderate/declining obesity, and non-obese; these groups had distinct risk profiles. Second, prediction analyses favored developmental programming explanations for obesity, including evidence even in early childhood that both low- and high birth weight was associated with stable obesity. There was no indication that pre- and perinatal and postnatal factors predicted obesity differently in non-minority and minority children. Discussion: Factors derived from the developmental programming model of obesity overlapped with, but predicted early onset obesity independently from, risks associated with social determinant models of obesity.